Monetary policy, macroprudential policy, and financial stability - David Martinez-Miera; Rafael Repullo (European Central Bank (ECB), 2019)
This paper reexamines from a theoretical perspective the role of monetary and macroprudential policies in addressing the build-up of risks in the financial system. We construct a stylized general equilibrium model in which the key friction comes from a moral hazard problem in firms' financing that banks' equity capital serves to ameliorate. Tight monetary policy is introduced by open market sales of government debt, and tight macroprudential policy by an increase in capital requirements. We show that both policies are useful, but macroprudential policy is more effective in fostering financial stability and leads to higher social welfare.
Keywords: G21; G28; E44; E52; 330; Bank monitoring; intermediation margin; monetary policy; macroprudential policy; capital requirements; financial stability